Policy Development Corporate Social Responsibility (CSR) based on Village Sustainable Development Goals (SDGs) in Bukit Batu District Bengkalis Regency - Mashur, Dadang; Zulkarnaini, Zulkarnaini; Sadad, Abdul; Meiwanda, Geovani; Rusli, Zaili (Iapa Proceedings Conference, 2023)
Current Corporate Social Responsibility (CSR) policies are often judged to be less targeted and unsustainable, causing disappointment to the community and government. In order for this CSR policy to be right on target and sustainable, then it needs to be based on the policy of accelerating the achievement of the Village Sustainable Development Goals (SDGs). Bengkalis Regency currently has one large company, namely PT. Pertamina Sungai Pakning which is committed to the implementation of CSR. The company has made a CSR policy from 2014, but this CSR policy has not been based on the Village SDGs. The purpose of this study is to develop CSR policies based on Village SDGs in order to assist villages in accelerating the achievement of national development goals. This study uses a qualitative method. The results of the study found that the development of CSR policies can be formulated using an incremental policy model by maintaining the fields of education, health, the environment and adding several fields, namely the economic, social, institutional and technological fields which have implications for the objectives of the Village SDGs. This policy can be realized through charity programs, infrastructure, capacity building, and community empowerment.